THE ROLE OF SMALL AND MEDIUM-SIZED BUSINESSES IN THE SOCIO-ECONOMIC DEVELOPMENT OF COMPANY TOWNS - E. V. Reznikova (Real Economics Publishing House, 2014)
The development of small and medium enterprises (SME) plays an important role in the comprehensive modernization of the economy of single-industry towns, acting as a factor of its growth and diversification. The analysis of the dynamics of the development of SME of non-diversified municipal formations and directions of its state support was made, suggestions on the monitoring organization of statistical factors of SME in single-industry towns and on the development of comprehensive investment plans on modernization of single-industry towns were made in a part of the development and support of small and medium businesses in single-industry towns.